Prevalência de triatomíneos (Hemíptera: Reduviidae: Triatominae) infectados por Trypanosoma cruzi: sazonalidade e distribuição na região Ciénega do Estado de Jalisco, México Prevalence of triatomines (Hemíptera: Reduviidae: Triatominae) infected by Trypanosoma cruzi: seasonality and distribution in the Ciénega region of the State of Jalisco, Mexico - César Gómez-Hernández (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
As características físico-geográficas da região Ciénega, Jalisco, México a tornam propícia para transmissão do Trypanosoma cruzi, causador da doença de Chagas. Este trabalho caracteriza a prevalência de triatomíneos infectados pelo parasita, sua sazonalidade e distribuição nesta região. Foram analisados 328 triatomíneos no período de janeiro de 2005 a junho de 2007 procedentes de 13 municípios da região, sendo abril, maio e junho os meses de maior captura. Dos triatomíneos analisados, 57,3% foram positivos para Trypanosoma cruzi, correspondendo 15,4% para a área urbana e 84,6% para a área rural. A espécie mais freqüente foi Triatoma longipennis e a mais parasitada foi Triatoma barberi com índice de infecção de 83,3% quando comparada a Triatoma longipennis (67,5%) (p<0,05). A infecção natural dos vetores capturados pode indicar alta exposição das pessoas ao Trypanosoma cruzi. O achado recente do Triatoma dimidiata positivo nesta região, sugere a adaptação de novas espécies às condições ecológicas destas populações. The physical and geographical characteristics of the Ciénega region, Jalisco, Mexico make it suitable for transmission of Trypanosoma cruzi, the causative agent for Chagas disease. This study characterizes the prevalence of triatomines infected by this parasite, their seasonality and their distribution in this region. A total of 328 triatomines were evaluated between January 2005 and June 2007, from 13 municipalities in the region. April, May and June were the months with the highest capture levels. Among the triatomines examined, 57.3% were positive for Trypanosoma cruzi, corresponding to 15.4% in urban areas and 84.6% in rural areas. The species with greatest prevalence was Triatoma longipennis and the species with the highest parasitism rate was Triatoma barberi, with an infection rate of 83.3%, whereas the rate for Triatoma longipennis was 67.5% (p<0.05). This natural infection in the captured vectors may indicate that individuals in this region have high exposure to Trypanosoma cruzi. The recent findings of positive Triatoma dimidiata in this region suggest that new species are becoming adapted to the ecological conditions of these populations.